Pengolahan Bittern Sebagai Pembentuk Pupuk Struvite Menggunakan Reaktor Sekat Secara Sinambung - Herdiana Septiani; Nikmatuz Zahra; Sutiyono; Luluk Edahwati (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2020)
Waste salt or bittern is the residual liquid from the salt formation which can not be precipitated again or also can be obtained from the washing water remaining in the purification process. Bittern contains salt such as MgCl2, MgSO4, KCl, and Br2. From the various minerals contained in the bittern, one of the minerals used as the basic ingredient of making struvite fertilizer, named Magnesium. Bittern has not been utilized significantly, this has become one of the goals and benefits of our research, which is making struvite fertilizer using salt waste, which will add up to it’s economic value. Struvite mineral can also be applied in agriculture such as raw material fertilizer, because struvite fertilizer is very beneficial for the growth and development of the plant. The most beneficial characteristic of struvite fertilizer is the slow release of nutrients so it will lessen fertilizer application on plants. Struvite has a very small solubility in water that is 0.02 gr / 100 ml at 0 ºC. Struvite solution (MAP) can be formed from phosphoric acid, ammonium hydroxide, and bittern or salt waste as a source of magnesium with a molar ratio of 2: 1: 1. PH variations carried out include 7 to 11 and the reactor intake air velocity in the range of 0.25-1.25 l / min in a fixed column operated reactor. The resulting dry sludge was analyzed by XRD method for mineral characterization and SEM to determine the composition and morphology of the crystals..